Career Competencies and Career Choice among Technical and Vocational Students: A Thematic Meta-Analysis (Architecture Image Studies, 2025)
Technical and Vocational Education and Training (TVET) has undergone significant transformation to produce a skilled workforce aligned with the needs of industry. However, in navigating an increasingly complex employment landscape, students are required to possess not only academic qualifications and technical competencies but also soft skills, personal qualities, and comprehensive career readiness. Therefore, this study aims to explore in greater depth the elements of career readiness skills and their importance in assisting students in making informed career choices. An in-depth analysis was conducted through a comprehensive review of prominent literature related to career readiness, career readiness skills, and career decision-making. The findings identified several key skill elements essential for developing career readiness, including student skills and qualities, technological and professional knowledge and competencies, entrepreneurial skills, and self-efficacy. These elements should be prioritized by TVET institutions through early exposure and interventions to better prepare students for appropriate career selection. This study also proposes a career readiness model based on the literature analysis, which can serve as a practical guide for institutions involved in technical and vocational education. It also adds value to the effort of producing highly skilled, competent, and quality human capital that meets current labour market demands.